Keterampilan Dasar Mengajar Mahasiswa Melalui Peer Teaching Pada Mata Kuliah Pembelajaran Mikro - Wulandari, Kartika; Pertiwi, Novia Ayu Sekar; Prihatiningtyas, Suci (JoEMS (Journal of Education and Management Studies), 2023)
This study aims to determine the basic skills of teaching students through peer teaching in micro learning courses in the Physics Education Study Program, KH University. A. Wahab Hasbullah Jombang in semester 6 with 8 students. Basic teaching skills are seen based on learning tools made based on the 2018 revised 2013 Curriculum which are then implemented through peer teaching and monitored by the implementation sheet of the learning process. The learning tools made consist of a Learning Implementation Plan (RPP) with learning scenarios. The research data were analyzed using a descriptive qualitative approach. The results showed that the ability of students to prepare lesson plans and learning scenarios in the criteria was very good with an average of 4.5. Meanwhile, basic teaching skills based on the implementation of lesson plans and learning scenarios during peer teaching are in poor criteria with average. 3.1. It is necessary to do peer teaching repeatedly on cognate subjects so that the basic skills of teaching students are getting better.